Penerapan Toleransi di Mata Pelajaran Olahraga di SDN 060913 - Sabrina Abigail; Nova Ritonga; Khaila Waldi; Muharram Irfan Padang; Akmalludin Hasibuan; Elisa Agustinus Gulo (Journal Innovation In Education, 2024)
The application of tolerance in education, including in sports subjects, plays an important role in shaping the character of students who respect differences. Sports as a medium for social interaction presents competitive situations that often involve various social backgrounds, cultures, and physical abilities of students. This study aims to analyze the application of tolerance values ​​in sports learning activities in schools, as well as their impact on students' attitudes and behavior. Through a qualitative approach, this study involved direct observation in several schools and interviews with sports teachers and students. The results of the study showed that when tolerance values ​​such as mutual respect, cooperation, and fairness were applied in sports learning, there was a significant increase in discipline, mutual respect, and teamwork among students. In conclusion, sports learning that prioritizes tolerance can have a positive impact on the formation of inclusive attitudes and better social relationships among students.